Conversations : The Journal of Cavellian Studies 5 - Branco, Sérgio Dias (2017)
This issue, which deals with politics and aesthetics (i.e. philosophy and poetry), features long political-philosophical exegesis on the promise of Cavellian praxis (in the classroom and beyond) and short pieces of Cavellian inflected poetry.